Transformative impact of blockchain technology and smart contracts on dispute resolution: legal challenges and other implications. - Christie, David; Mante, Joseph; Mak, Charles Ho Wang (Artificial intelligence: its applications, academic and practical legal implications, 2024)
This paper comprehensively analyses the potential of blockchain technology and smart contracts to revolutionise dispute resolution. As dispute resolution methods evolve, blockchain and smart contracts, which offer efficiency, transparency, and fairness, are becoming more critical. That is especially the case in mediation and construction adjudication, which are less traditionally formal and tend to be carried through much more quickly than other forms of dispute resolution. The opportunity of blockchain comes from its ability to demonstrate a tamper-proof, clear record, reducing risks of misunderstanding and bias. This facilitates the transfer and verification of evidence both in the carrying out of projects and during dispute resolution processes. Smart–digital contracts with terms coded indirectly- allow for automated contract enforcement. They execute automatically upon meeting specific conditions. This automation brings a new efficiency level, cutting the time and costs of conventional dispute resolution. Nonetheless, integrating blockchain and smart contracts in dispute resolution faces several challenges. The current limited understanding and acceptance of these technologies in the legal sector is an imminent issue. Legislative changes are necessary to provide a solid legal framework for these technologies in legal processes and to address potential inconsistencies of approach. Such reform requires strong cooperation among lawmakers, technologists, and legal experts to ensure implementation that adheres to legal and ethical norms and ensures that the technologies can be applied with confidence by the stakeholders within the process. This collective effort is crucial for seamlessly integrating blockchain and smart contracts into legal frameworks.
Publisher: Kuwait International Law School ISSN 2410-2237 https://rgu-repository.worktribe.com/output/2343788/transformative-impact-of-blockchain-technology-and-smart-contracts-on-dispute-resolution-legal-challenges-and-other-implications
Keywords: Blockchain technology; Dispute resolution methods; English law; Smart contracts

The impact of blockchain and smart contracts on dispute settlement: a case for mediation. - Mak, Charles Ho Wang; Mante, Joseph (Dispute settlement: the past, present and future dimensions, 2023)
The research is premised on two important developments, accelerating technological innovation and shifts in dispute resolution paradigms. These advancements offer an innovative framework for dispute avoidance and a more efficient, transparent process for resolving conflicts, particularly in commercial settings. To make this case, we use blockchain technology and smart contracts as technological exemplars, and mediation as an example of dispute resolution mechanism that can be positively impacted by the use of the relevant technology. The potential of these technologies to promote dispute avoidance and the emerging legal frameworks for resolving blockchain technology and smart contract disputes were also explored. We also examine how blockchain technology and smart contracts can be integrated into the mediation process, the advantages, challenges, and possible solutions.
https://rgu-repository.worktribe.com/output/2086138/the-impact-of-blockchain-and-smart-contracts-on-dispute-settlement-a-case-for-mediation
Keywords: Blockchain technology; Dispute resolutions; Disputes; Smart contacts; Technological innovation

The Application of CISG in International Arbitration - Cisár, Ivan (Current Issues of International Commercial Arbitration, 2017)
International arbitration allows great flexibility of the parties to structure their whole relationship. One of the key factors is the choice of the law applicable to the substance of the relationship. CISG is intended for the regulation of such relations between international businessmen. This paper builds on the empirical evidence of the International Arbitration Surveys conducted among various groups of practitioners on their reasoning con cerning choice of law applicable to the substance of the relationship and argues that although CISG is not chosen by them frequently (or arguably not chosen at all), this “omission” is not warranted.
Keywords: CHOICE OF APPLICABLE LAW; CISG; INTERNATIONAL ARBITRATION

The impact of non-operationalisation of the SADC protocol and international transport agreements on cross border road transport movement in the SADC region - Monyepao, Kaine (Working Together to Deliver - Sakha Sonke, 2015)
The failure by Sothern African Development Community (SADC) countries to fully implement the SADC Protocol on Transport, Communications and Meteorology (the Protocol) and bilateral agreements in regard to road transport negatively impacts the seamless movement of cross border road transport and significantly contributes to the challenges faced by the cross border industry as a whole. The full implementation of the Protocol in regard to road transport, and bilateral agreements would lead to efficient cross border transport regulation and transportation and in turn culminate in reduction of challenges facing the sector. This would lead to reduction of transportation costs, improvement in productivity, and accelerated growth in intra-regional trade, regional economic integration and overall SADC socio-economic development. This paper outlines the extent to which the provisions of the Protocol and bilateral agreements have been implemented by SADC countries and the key challenges emanating from the partial operationalisation of the instruments. The paper is based on findings from engagements with key government and private sector stakeholders in the regional transport environment and various research conducted by the C-BRTA between 2011 and 2014. The partial operationalisation of the instruments has resulted in disjointed regulatory frameworks and inability to: holistically address corridor constraints/ non-tariff barriers, facilitate seamless cross border movements, facilitate liberalisation of access to transport markets in the region, harmonise standards and procedures, and facilitate economic growth and trade between SADC countries. It is possible for the SADC region to realise the aspirations set out in the Protocol and bilateral agreements, and this paper outlines some of the solutions. To begin with, there is need for SADC countries to embrace the need to eradicate the existing self-centric regulatory approach limited to micro-needs and market protectionism. This would need to be underpinned by strong orientation towards the need to achieve macro benefits emanating from a regional perspective in regard to regulating cross border road transport movement. Taking off from this departure point, SADC countries can objectively establish a solid ground towards fully operationalising the Protocol and bilateral agreements. This paper outlines some of the interventions that can be implemented to ensure SADC countries fully operationalise the provisions of the Protocol on transport and bilateral agreements.
Accepted: 2016-11-08T12:11:22Z Artwork Medium: PDF Interview Medium: PDF
Keywords: Southern African Transport Conference; Transportation

Internal Audit Characteristics and Quality of Accounting Information in Nigeria - Ogundana, Oyebisi Mary; Ojeka, Stephen; Ojua, Michael; Nwaze, Chukwu (Conference Proceedings, 2015)
The basic goal of Accounting is to provide enabling accounting information for reliable decision-making. The quality level of this accounting information comes from the company's governance practices, thereby emphasizing the importance of corporate governance in companies. Recently, following the financial crises resulting in accounting scandals, attention has been moving towards Internal Audit Function as an important factor in the structure of Corporate Governance. This paper therefore examined the extent of the relationship between internal audit function and the quality of accounting information of companies. The study adopted the Survey research design. The research instrument employed was Questionnaire which was administered to internal auditors of the “Big Four”. Linear regression analysis was employed in the analysis of the data collected with the use of Statistical Packages for Social Sciences (SPSS). The results revealed that there is a significant relationship between the internal audit characteristics and the quality of accounting information. It was recommended that in order to provide credibility to the financial statement, there should be a law in place mandating attachment of internal auditors report to the financial statement
Keywords: Accounting quality; Accounting report; Corporate governance; Fraud; internal auditing

Multi-Membership and the Effectiveness of Regional Trade Agreements in Western and Southern Africa: A Comparative Study of ECOWAS and SADC - Afesorgbor, Sylvanus Kwaku; Van Bergeijk, Peter A. G. (Proceedings of the German Development Economics Conference, 2011)
Using a gravity model for 35 countries and the years 1995-2006 we estimate the impact of regional trade agreements in Africa (in particular ECOWAS and SADC) and compare this to the a benchmark of North South trade integration (Europe‟s preferential trade agreement). We find that  ECOWAS and SADC membership significantly increases bilateral trade flows (and by more than for example preferential trade agreements with the EU do),  SADC membership has a stronger impact compared to ECOWAS and  that the impact of multi-membership critically depends on the characteristics of the overlapping RTA We find a positive impact if an additional membership complements the integration process of the original RTA: overlapping memberships had a significant positive effect on bilateral trade within the ECOWAS bloc but it is insignificant for SADC.

The Role of International Economic Law in Africa - Obale, Offah Ako (Social Science Research Network, 2008)
International Economic law (IEL) has a specific role to play in a complex modern Africa. The underdeveloped state of trade law regimes in Africa is arguably a reflection and product of the low level of commercial activity. The reverse is equally true in that underdevelopment in commercial activity on the continent is a reflection and product of the minimal role played thus far by international economic law.
Keywords: AEC; Africa; African; African Economic Community (AEC); Doha; Globilisation; International Economic Law; OHADA; Trade law; WTO